Experiences and Suggestions on Atmospheric Corrosion Prevention in Nuclear Power Projects - TAO Xin-lei, WANG Yu, CHU Zhao-xin, DU Chao (Cailiao Baohu, 2021)
The nuclear power plants under construction and operation in China are all located in the coastal area, and the atmospheric environment mostly belongs to the typical marine atmospheric environment with high corrosiveness.Corrosion of equipment and materials in nuclear power projects has always been a key concern of nuclear power plants under construction and operation, which is related to the economy and safety of nuclear power projects.In particular, there is no special anti-corrosion standard for equipment exposed to outdoor atmospheric enviroment in nuclear power industry.In this paper, the current anti-corrosion measures of nuclear power projects with the general standards of anti-corrosion industry were compared.Taking blackening and phosphating treatment as examples, the effects and shortcomings of the temporary anti-corrosion measures for nuclear power fasteners were analyzed, the gap was found out, and the suggestions and the improvement measures were puts forward, which could provide a reference for the anti-corrosion work of nuclear power projects.